A method for synergistically spheroidizing primary silicon in hypereutectic aluminum-silicon alloys

CN122913505APending Publication Date: 2026-10-16WUXI ZHONGKE ZUOYUAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611320491.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

其中,变质处理主要通过促进异质形核或改变Si晶体的择优生长行为实现初生Si细化,但容易受到变质元素烧损、偏析、相互“毒化”以及熔体保温时间的影响,且过量添加可能形成脆性金属间化合物;外场处理对设备结构、处理范围和工艺稳定性要求较高,难以保证大批量生产中熔体各区域处理效果一致;单纯提高冷却速率虽可减小初生Si尺寸,但获得的初生Si仍可能保留明显棱角,且不同尺寸液滴或不同位置熔体的冷却条件差异较大,容易造成组织不均匀;后续高温热处理能够在一定程度上促进初生Si圆钝化或球化,但通常需要较长保温时间,存在能耗高、晶粒粗化以及初生Si聚并长大的问题

Benefits of technology

[0017]This invention suppresses the rapid growth of primary Si along specific crystal orientations and the formation of sharp edges by controlling the number of nucleations of primary Si, interfacial energy, preferred growth mode, and atomic migration process at the solid-liquid interface. As a result, a primary Si microstructure with small size, round morphology, and uniform distribution is directly obtained during the rapid solidification stage of the powder. This reduces the dependence on long-term subsequent spheroidizing heat treatment and improves the consistency of the hypereutectic Al-Si alloy powder microstructure and the comprehensive performance of its subsequent products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913505A_ABST
    Figure CN122913505A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of method for the primary silicon in peritectic aluminum silicon alloy of synergistic spheroidization, belong to material science and technology field. Industrial aluminum ingot, silicon block are put into smelting furnace and heated, Al-Cr intermediate alloy is put in, and stirring is kept warm;Hydrogen and inclusion floatation, static setting removes slag, after cooling, Al-Bi intermediate alloy is put in;Alloy melt is guided to atomizing nozzle, and high-pressure high-purity inert gas is used to break liquid stream to form liquid alloy microdroplet, and after droplet cooling, peritectic aluminum silicon alloy powder is obtained by collection and screening.The Si particle roundness of the Si particle roundness obtained by the present application is improved, there is no coarse platelet, acicular silicon, and subsequent heat treatment process is not needed, and production cost is reduced.Si spheroidization in peritectic Al-Si alloy powder can weaken the defects of Al-Si interface stress concentration, and improve tensile strength and fracture elongation.The whole preparation process of the present application is non-toxic reaction, does not involve rare earth element, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for synergistic spheroidization of primary silicon in hypereutectic aluminum-silicon alloys, specifically a method for synergistic spheroidization of primary silicon in hypereutectic aluminum-silicon alloys using Bi-Cr interface control and rapid spray solidification, which is used for the preparation of electronic packaging materials and wear-resistant components, and belongs to the field of materials science and technology. Background Technology

[0002] Hypereutectic Al-Si alloys possess advantages such as low density, low coefficient of thermal expansion, good wear resistance, and good dimensional stability, making them widely used in electronic packaging, aerospace, automotive engines, and precision structural components. However, during solidification, they are prone to forming coarse, angular, plate-like, blocky, or polyhedral primary Si phases. These primary Si phases exhibit significant differences in elastic modulus and thermal expansion properties compared to the aluminum matrix. Their sharp corners and edges easily cause stress concentration and microcrack initiation, thereby reducing the alloy's plasticity, fatigue performance, machinability, and service reliability.

[0003] Currently, the refinement and morphology control of primary Si mainly employs the addition of modifying elements such as P, rare earth elements, Cr, Na, and Bi, along with ultrasonic, electromagnetic, or mechanical stirring, and techniques such as rapid solidification, spray forming, powder metallurgy, and subsequent heat treatment. Among these, modification treatment primarily refines primary Si by promoting heterogeneous nucleation or altering the preferred growth behavior of Si crystals. However, it is susceptible to the effects of modifying element burn-off, segregation, mutual poisoning, and melt holding time; excessive addition may also form brittle intermetallic compounds. External field treatment places high demands on equipment structure, processing range, and process stability, making it difficult to ensure consistent treatment effects across different areas of the melt in mass production. While simply increasing the cooling rate can reduce the size of primary Si, the resulting primary Si may still retain noticeable sharp edges, and the cooling conditions for droplets of different sizes or at different locations of the melt vary significantly, easily leading to inhomogeneous microstructure. Subsequent high-temperature heat treatment can promote the rounding or spheroidization of primary Si to some extent, but it typically requires long holding times, resulting in high energy consumption, grain coarsening, and the agglomeration and growth of primary Si. Therefore, existing technologies are still unable to simultaneously achieve sufficient refinement, low angularity, near-spherical shape, and uniform distribution of primary Si within a wide range of Si content and stable industrial process windows. Summary of the Invention

[0004] The purpose of this invention is to overcome the above-mentioned shortcomings and provide a method for synergistically spheroidizing primary silicon in hypereutectic aluminum-silicon alloys. This method utilizes Bi to regulate surface energy during the rapid cooling process of jet powdering, thereby synergistically achieving Si particle refinement and equiaxed spheroidization.

[0005] The technical solution of this invention, a method for synergistically spheroidizing primary silicon in hypereutectic aluminum-silicon alloys, comprises the following steps by weight: (1) Take 12-50 parts of silicon blocks and 42-87 parts of aluminum ingots and homogenize them at 600-800℃ for 20-40 minutes under inert gas protection, keep warm for 30-50 minutes, and then let stand to remove slag to obtain melt; (2) Heat the melt obtained in step (1) to 700-900℃, stir and keep warm, add 0.5-3 parts of Al-Cr master alloy (Cr mass fraction 2%-20%), stir to make Cr evenly dispersed in the melt, and keep warm for 15-25 minutes; (3) Inert gas is introduced into the melt obtained in step (2), and the surface scum is removed after standing. (4) Cool the melt obtained in step (3) at a rate of 3-10℃ / min. Stop cooling when the temperature drops to 670-690℃ and keep it at that temperature for 5-20 min. (5) Add 0.5-2 parts of Al-Bi master alloy Al-10Bi to the melt obtained in step (4) and stir continuously for 5-15 minutes to make it evenly mixed with the melt; (6) The above melt is guided to the atomizing nozzle, and the droplets are rapidly cooled to complete solidification at the same time as the liquid is discharged to obtain the alloy; (7) Collect and sieve the solidified alloy powder to obtain hypereutectic aluminum-silicon alloy.

[0006] Furthermore, the composition of the prepared hypereutectic aluminum-silicon alloy powder by mass percentage is as follows: Si 12%~50%, Bi 0.06%~0.18%, Cr 1.0%~8.0%, with the balance being Al.

[0007] Furthermore, in step (2), the melt is heated to 50-120 °C above the liquidus temperature of the Al-Si-Cr alloy.

[0008] Furthermore, in the Al-Cr master alloy described in step (2), the mass fraction of Cr is 2%-20%.

[0009] Furthermore, the inert gas is nitrogen, helium, or argon.

[0010] Further, in step (6), the liquid is atomized using an atomizing nozzle; when the liquid is discharged, a high-pressure inert gas is used to break the liquid flow to form liquid alloy droplets, so that the droplets are rapidly cooled and completely solidified during flight.

[0011] Furthermore, the liquid outlet temperature in step (6) is 620-680 ℃; the liquid outlet temperature is 10-50 ℃ lower than the cooling endpoint in step (4).

[0012] Furthermore, in step (6), the atomization pressure is 0.8-3.0 MPa, the mass flow ratio of high-pressure inert gas to alloy melt is 0.8-3.0, the inner diameter of the melt guide tube is 2-8 mm, and the mass flow rate of alloy melt is 2-20 kg / min.

[0013] Furthermore, in step (6), in order to ensure that the droplets are completely cooled, the vertical distance between the outlet of the atomizing nozzle and the inlet of the collecting device is 1.5-3.5m.

[0014] Furthermore, the alloy powder has a particle size of 10-250 μm, the average equivalent circle diameter of the primary Si particles inside the powder particles is not greater than 30 μm, the average aspect ratio is not greater than 1.8, and the average roundness is not less than 0.60.

[0015] This invention employs an inert atmosphere melting furnace, a high-pressure gas atomization powder-making device, a cyclone separator, and a hot isostatic pressing device. The high-pressure gas atomization powder-making device consists of an atomization zone and a cavity. The atomization zone comprises a central melt conduit (4 mm inner diameter) and an outer annular gas nozzle, using a tight coupling design, forming the atomization zone below the conduit outlet. The space between the atomization zone and the cavity wall serves as a flight cooling zone. Powder meeting the particle size requirements is sieved using a cyclone separator, then encapsulated and vacuum-sealed, followed by hot isostatic pressing to obtain the alloy product.

[0016] This invention utilizes the induction of nucleation by Cr during slow cooling and the regulation of surface energy by Bi during rapid cooling in jet powdering to synergistically achieve Si particle refinement and equiaxed spheroidization. During the cooling and solidification stage, the slow solidification of the melt induces the CrSi2, τ phase (…). , Precipitation increases the number of nuclei; during rapid jet cooling, the liquid-solid interface energy at the (110) crystal plane of Si is the highest, and Bi preferentially accumulates at the Al-Si solid-liquid interface, reducing the relative growth rate difference between different crystal planes of nascent Si. By synergistically controlling the stepwise addition of Cr before Bi, the melt cooling rate, and the rapid solidification state of the droplets, the anisotropic growth of nascent Si crystals is suppressed. According to the Newtonian cooling heat transfer model: dT / dt= Where dT / dt is the cooling rate. The initial temperature of the molten droplet. Nitrogen or argon gas at room temperature. The density of the alloy, The specific heat capacity of the liquid alloy. The droplet diameter is the limiting factor. The cooling rate is primarily controlled by the droplet diameter, which is influenced by atomizing gas pressure, melt temperature, and nozzle orifice diameter.

[0017] This invention suppresses the rapid growth of primary Si along specific crystal orientations and the formation of sharp edges by controlling the number of nucleations of primary Si, interfacial energy, preferred growth mode, and atomic migration process at the solid-liquid interface. As a result, a primary Si microstructure with small size, round morphology, and uniform distribution is directly obtained during the rapid solidification stage of the powder. This reduces the dependence on long-term subsequent spheroidizing heat treatment and improves the consistency of the hypereutectic Al-Si alloy powder microstructure and the comprehensive performance of its subsequent products.

[0018] The beneficial effects of this invention are as follows: The Si particles prepared by this invention have improved sphericity, with no coarse plate-like or needle-like silicon particles, eliminating the need for subsequent heat treatment processes and reducing production costs. The spheroidization of Si in the hypereutectic Al-Si alloy powder weakens the stress concentration defects at the Al-Si interface, improving tensile strength and elongation at break. The entire preparation process of this invention involves no toxic chemical reactions and does not involve rare earth elements, making it suitable for industrial production. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 SEM image of the alloy prepared in Example 1.

[0021] Figure 2 SEM image of the alloy prepared in Example 2.

[0022] Figure 3 SEM image of the alloy prepared in Example 3.

[0023] Figure 4 SEM images of the alloy prepared in Comparative Example 1.

[0024] Figure 5 SEM image of the alloy prepared in Comparative Example 2.

[0025] Figure 6 SEM image of the alloy prepared in Comparative Example 3. Detailed Implementation

[0026] Example 1

[0027] The raw materials are taken in parts by weight, including 78.4 parts aluminum ingot, 20 parts Si, 0.8 parts Al-10Bi master alloy, and 0.8 parts Al-10Cr master alloy.

[0028] Industrial aluminum ingots and silicon blocks were added to a melting furnace and heated to 700°C under argon protection. After the matrix melt became homogeneous, it was held at this temperature for 40 minutes and allowed to stand to remove slag. The temperature was then raised to 800°C, and an Al-10Cr master alloy was added. The mixture was stirred to ensure Cr was evenly dispersed within the melt, and held for 20 minutes. Inert gas was then introduced into the melt for hydrogen removal and inclusion flotation. After standing, surface slag was removed. The temperature was then lowered to 690°C at a rate of 8°C / min and held for 10 minutes. An Al-10Bi master alloy was then added, and the mixture was stirred continuously for 10 minutes to ensure homogeneity. The high-temperature alloy melt is guided to an atomizing nozzle. The melt temperature is not lower than 680℃. A high-pressure, high-purity N2 stream at 1.5 MPa is used to break up the liquid, forming liquid alloy microdroplets. The mass flow ratio of the atomizing gas to the alloy melt is 1.5. The inner diameter of the guide tube is 4 mm, and the melt mass flow rate is 2 kg / min. A 1.5 m long nitrogen-protected cooling zone is set between the outlet of the atomizing nozzle and the inlet of the powder collection device to ensure complete solidification of the atomized droplets before entering the powder collection device. After cooling, the powder is collected and sieved under an inert atmosphere to obtain hypereutectic aluminum-silicon alloy powder. The obtained powder is then encapsulated under vacuum and hot isostatically pressed at 490℃, 120 MPa, and 2 h to obtain an alloy block.

[0029] The resulting alloy, by mass percentage, consists of 20 wt% Si, 0.08 wt% Bi, 0.08 wt% Cr, with the balance being Al.

[0030] The obtained product experimental data are shown in Table 1, and the SEM images are shown in Table 2. Figure 1 As shown.

[0031] Example 2

[0032] The raw materials are calculated by weight, including 67.3 parts aluminum ingot, 30 parts Si, 1.2 parts Al-10Bi master alloy, and 1.5 parts Al-10Cr master alloy.

[0033] Industrial aluminum ingots and silicon blocks were added to an intermediate frequency furnace and heated to 780 °C, held for 40 min until the matrix melt was homogeneous, held for another 40 min, and allowed to stand to remove slag. The temperature was then raised to 850 °C, and an Al-10Cr master alloy was added. Stirring was performed to ensure Cr was evenly dispersed within the melt, and the temperature was held for 25 min. Inert gas was then introduced into the melt for hydrogen removal and inclusion flotation. After standing, surface slag was removed. The temperature was then lowered to 790 °C at a rate of 5 °C / min and held for 15 min. An Al-10Bi master alloy was then added, and stirring was continued for 10 min to ensure uniform mixing. The high-temperature alloy melt is guided to an atomizing nozzle, with a melt temperature not lower than 770 °C. A high-pressure, high-purity N2 stream at 2.2 MPa is used to break up the liquid, forming liquid alloy microdroplets. The mass flow ratio of the atomizing gas to the alloy melt is 2.0. The inner diameter of the guide tube is 4 mm, and the melt mass flow rate is 3 kg / min. A 2.0 m long nitrogen-protected cooling zone is set between the outlet of the atomizing nozzle and the inlet of the powder collection device to ensure complete solidification of the atomized droplets before entering the powder collection device. After cooling, the powder is collected and sieved under an inert atmosphere to obtain alloy powder. The obtained alloy powder is then encapsulated under vacuum and hot isostatically pressed at 490 °C, 120 MPa, and 2 h to obtain an alloy block.

[0034] The resulting alloy, by mass percentage, consists of 30 wt% Si, 0.12 wt% Bi, 0.15 wt% Cr, with the balance being Al.

[0035] The obtained product experimental data are shown in Table 1, and the SEM images are shown in Table 2. Figure 2 As shown.

[0036] Example 3

[0037] The raw materials are calculated by weight, including 50.9 parts aluminum ingot, 45 parts Si, 1.6 parts Al-10Bi master alloy, and 2.5 parts Al-10Cr master alloy.

[0038] Industrial aluminum ingots and silicon blocks were added to an intermediate frequency furnace and heated to 900 °C, held for 40 min until the matrix melt was homogeneous, held for another 40 min, and allowed to stand to remove slag. The temperature was then raised to 960 °C, and an Al-10Cr master alloy was added. Stirring was performed to ensure Cr was evenly dispersed within the melt, and the temperature was held for 10 min. Inert gas was then introduced into the melt for hydrogen removal and inclusion flotation. After standing, surface slag was removed. The temperature was then lowered to 910 °C at a rate of 3 °C / min and held for 20 min. An Al-10Bi master alloy was then added, and stirring was continued for 10 min to ensure uniform mixing. The high-temperature alloy melt is guided to an atomizing nozzle. The melt temperature is not lower than 880 °C. A high-purity N2 jet at 3.0 MPa is used to break up the liquid, forming liquid alloy microdroplets. The mass flow ratio of the atomizing gas to the alloy melt is 3.0. The inner diameter of the guide tube is 5 mm, and the melt mass flow rate is 4 kg / min. A 3.0 m long nitrogen-protected cooling zone is set between the outlet of the atomizing nozzle and the inlet of the powder collection device to ensure complete solidification of the atomized droplets before entering the powder collection device. After cooling, the powder is collected and sieved under an inert atmosphere to obtain alloy powder. The obtained alloy powder is then encapsulated under vacuum and hot isostatically pressed at 490 °C, 120 MPa, and 2 h to obtain an alloy block.

[0039] The resulting alloy, by mass percentage, consists of 45 wt% Si, 0.16 wt% Bi, 0.25 wt% Cr, with the balance being Al.

[0040] The obtained product experimental data are shown in Table 1, and the SEM images are shown in Table 2. Figure 3 As shown.

[0041] Comparative Example 1 The raw materials are calculated by weight, including 68.8 parts aluminum ingot, 30 parts Si, and 1.2 parts Al-10Bi master alloy.

[0042] Industrial aluminum ingots and silicon blocks were fed into an intermediate frequency furnace and heated to 850 °C, held for 40 min, and then inert gas was introduced into the melt for hydrogen removal and inclusion flotation. After settling, surface slag was removed. The temperature was then lowered to 790 °C at a rate of 3 °C / min and held for 15 min. An Al-10Bi master alloy was added and stirred continuously for 10 min to ensure uniform mixing. The high-temperature alloy melt was guided to an atomizing nozzle, with the melt temperature not lower than 770 °C. A 2.2 MPa high-pressure, high-purity N2 stream was used to break up the liquid, forming liquid alloy microdroplets. The mass flow ratio of the atomizing gas to the alloy melt was 2.0, the inner diameter of the guide tube was 4 mm, and the melt mass flow rate was 3 kg / min. A 2.0 m long nitrogen-protected cooling zone was set between the atomizing nozzle outlet and the powder collection device inlet to ensure complete solidification of the atomized droplets before entering the powder collection device. After cooling, the powder was collected and sieved under an inert atmosphere to obtain alloy powder. The obtained alloy powder was encapsulated under vacuum and hot isostatically pressed at 490 °C, 120 MPa, and 2 h to obtain an alloy block.

[0043] The resulting alloy, by mass percentage, consists of 30 wt% Si, 0.12 wt% Bi, and the balance being Al.

[0044] The obtained product experimental data are shown in Table 1, and the SEM images are shown in Table 2. Figure 4 As shown.

[0045] Comparative Example 2 The raw materials are calculated by weight, including 53.5 parts aluminum ingot, 45 parts Si, and 1.5 parts Al-10Cr master alloy.

[0046] Industrial aluminum ingots and silicon blocks were added to an intermediate frequency furnace and heated to 780 °C, held for 40 min, and after the matrix melt became homogeneous, held for another 40 min, and allowed to stand to remove slag. The temperature was then raised to 850 °C, and an Al-10Cr master alloy was added. The mixture was stirred to ensure Cr was evenly dispersed within the melt, held for 10 min, and inert gas was introduced into the melt for hydrogen removal and inclusion flotation. After standing, surface slag was removed. The temperature was then lowered to 790 °C at a rate of 5 °C / min, and held for 15 min. The high-temperature alloy melt is guided to an atomizing nozzle. The melt temperature is not lower than 770 °C. A high-pressure, high-purity N2 stream at 2.2 MPa is used to break up the liquid, forming liquid alloy microdroplets. The mass flow ratio of the atomizing gas to the alloy melt is 2.0. The inner diameter of the guide tube is 4 mm, and the melt mass flow rate is 3 kg / min. A 2.0 m long nitrogen-protected cooling zone is set between the outlet of the atomizing nozzle and the inlet of the powder collection device to ensure complete solidification of the atomized droplets before entering the powder collection device. After cooling, the powder is collected and sieved under an inert atmosphere to obtain alloy powder. The obtained alloy powder is then encapsulated under vacuum and hot isostatically pressed at 490 °C, 120 MPa, and 2 h to obtain an alloy block.

[0047] The resulting alloy, by mass percentage, consists of 30 wt% Si, 0.15 wt% Cr, and the balance being Al.

[0048] The obtained product experimental data are shown in Table 1, and the SEM images are shown in Table 2. Figure 5 As shown.

[0049] Comparative Example 3 The raw materials are calculated by weight, including 67.3 parts aluminum ingot, 30 parts Si, 1.2 parts Al-10Bi master alloy, and 1.5 parts Al-10Cr master alloy.

[0050] Industrial aluminum ingots and silicon blocks were added to an intermediate frequency furnace and heated to 780℃, held for 40 minutes until the matrix melt was homogeneous. After holding for another 40 minutes, the mixture was allowed to stand to remove slag. The temperature was then raised to 850℃, and an Al-10Cr master alloy was added. The mixture was stirred to ensure Cr was evenly dispersed within the melt, and held for 25 minutes. Inert gas was then introduced into the melt for hydrogen removal and inclusion flotation. After standing, surface slag was removed. The temperature was then lowered to 790℃ at a rate of 5℃ / min and held for 15 minutes. An Al-10Bi master alloy was then added, and the mixture was stirred continuously for 10 minutes to ensure homogeneity. The high-temperature alloy melt is guided to an atomizing nozzle. The melt temperature is not lower than 770℃. A high-pressure, high-purity N2 stream at 0.6 MPa is used to break up the liquid, forming liquid alloy microdroplets. The mass flow ratio of the atomizing gas to the alloy melt is 0.8. The inner diameter of the guide tube is 4 mm, and the melt mass flow rate is 5 kg / min. A 0.8 m long nitrogen-protected cooling zone is set between the outlet of the atomizing nozzle and the inlet of the powder collection device to ensure complete solidification of the atomized droplets before entering the powder collection device. After the powder cools, it is collected and sieved under an inert atmosphere. Then, it is encased in a vacuum and hot isostatically pressed at 490℃, 120 MPa, and 2 h to obtain an alloy block.

[0051] The resulting alloy, by mass percentage, consists of 30 wt% Si, 0.12 wt% Bi, 0.15 wt% Cr, with the balance being Al.

[0052] The obtained product experimental data are shown in Table 1, and the SEM images are shown in Table 2. Figure 6 As shown.

[0053] Table 1. Statistics on the average equivalent circle diameter, average aspect ratio, and average roundness of nascent Si (70 samples).

[0054] According to Table 1, by adjusting the mass fractions of Cr and Bi, the cooling rate after adding Al-Cr master alloy, the temperature at which Al-Bi master alloy is added, and the atomization powdering process conditions, a primary Si phase with an average aspect ratio of <1.5 and a roundness of >0.8 can be obtained. As the Si content increases, the size of the Si phase increases and the roundness decreases (Examples 1-3).

[0055] Adding only a single element, such as Bi (Comparative Example 1) or Cr (Comparative Example 2), or using spray-drying process parameters outside the aforementioned ranges, resulted in alloys with larger primary Si phase sizes, lower roundness (<0.8), and significantly increased aspect ratios compared to alloys with the same Si content (Example 2). Figure 4 It can be seen that the Si phases exhibit significant size differences, indicating that the lack of Cr makes it difficult to achieve a large amount of heterogeneous nucleation, and Si tends to aggregate and grow. Figure 5It can be seen that the Si phase is relatively flat and plate-like, with obvious gaps between it and the surrounding Al matrix. This indicates that the lack of Bi makes it difficult to suppress the anisotropic growth of the Si phase, resulting in many sharp edges and low roundness, which reduces the uniformity of Al coating on the Si phase during plastic flow. At the same time, the plate-like geometry will cause interfacial stress concentration, amplifying the thermal mismatch stress at the Si / Al interface, thus making debonding and voids more likely to occur.

[0056] If the spray powdering process is not within a suitable range (Comparative Example 3), even if the alloy composition is the same as in Example 2, if the gas pressure, gas-liquid ratio, and flight cooling distance in the spray powdering process are too low, it will be impossible to fix the fine and round Si phase structure through rapid solidification, which will still cause the Si phase size to increase and the roundness to decrease.

[0057] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0058] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for synergistically spheroidizing primary silicon in hypereutectic aluminum-silicon alloys, characterized by... The steps for weight measurement are as follows: (1) Take 12-50 parts of silicon blocks and 42-87 parts of aluminum ingots and homogenize them at 600-800 ℃ for 20-40 min under inert gas protection, keep warm for 30-50 min, and then let stand to remove slag to obtain melt; (2) Heat the melt obtained in step (1) to 700-900 ℃, stir and keep warm, add 0.5-3 parts of Al-Cr master alloy Al-10Cr, stir to make Cr evenly dispersed in the melt, and keep warm for 15-25 min; (3) Inert gas is introduced into the melt obtained in step (2), and the surface scum is removed after standing. (4) Cool the melt obtained in step (3) at a rate of 3-10℃ / min. Stop cooling when the temperature drops to 670-690℃ and keep it at that temperature for 5-20 min. (5) Add 0.5-2 parts of Al-Bi master alloy Al-10Bi to the melt obtained in step (4) and stir continuously for 5-15 minutes to make it evenly mixed with the melt; (6) The above melt is guided to the atomizing nozzle, and the droplets are rapidly cooled to complete solidification at the same time as the liquid is discharged to obtain the alloy; (7) Collect and sieve the solidified alloy powder to obtain hypereutectic aluminum-silicon alloy.

2. The method for synergistically spheroidizing primary silicon in a hypereutectic aluminum-silicon alloy as described in claim 1, characterized in that: The composition of the hypereutectic aluminum-silicon alloy powder prepared is as follows by mass percentage: Si 12%~50%, Bi 0.06%~0.18%, Cr 1.0%~8.0%, with the balance being Al.

3. The method for synergistic spheroidization of primary silicon in hypereutectic aluminum-silicon alloy as described in claim 1, characterized in that: In step (2), the melt is heated to 50-120 °C above the liquidus temperature of the Al-Si-Cr alloy.

4. The method for synergistic spheroidization of primary silicon in hypereutectic aluminum-silicon alloy as described in claim 1, characterized in that: In the Al-Cr master alloy described in step (2), the mass fraction of Cr is 2%-20%.

5. The method for synergistically spheroidizing primary silicon in a hypereutectic aluminum-silicon alloy as described in claim 1, characterized in that: The inert gas is nitrogen, helium, or argon.

6. The method for synergistic spheroidization of primary silicon in hypereutectic aluminum-silicon alloy as described in claim 1, characterized in that: Step (6) Use an atomizing nozzle to atomize the liquid; when the liquid is discharged, high-pressure inert gas is used to break the liquid flow to form liquid alloy droplets, so that the droplets are rapidly cooled and completely solidified during flight.

7. The method for synergistic spheroidization of primary silicon in hypereutectic aluminum-silicon alloy as described in claim 6, characterized in that: The liquid outlet temperature in step (6) is 620-680 ℃; the liquid outlet temperature is 10-50 ℃ lower than the cooling endpoint in step (4).

8. The method for synergistic spheroidization of primary silicon in hypereutectic aluminum-silicon alloy as described in claim 6, characterized in that: In step (6), the atomization pressure is 0.8-3.0 MPa, the mass flow ratio of high-pressure inert gas to alloy melt is 0.8-3.0, the inner diameter of the melt guide tube is 2-8 mm, and the mass flow rate of alloy melt is 2-20 kg / min.

9. The method for synergistic spheroidization of primary silicon in hypereutectic aluminum-silicon alloy as described in claim 6, characterized in that: In step (6), in order to ensure that the droplets are completely cooled, the vertical distance between the outlet of the atomizing nozzle and the inlet of the collecting device is 1.5-3.5m.

10. The method for synergistically spheroidizing primary silicon in a hypereutectic aluminum-silicon alloy as described in claim 2, characterized in that: The alloy powder has a particle size of 10-250 μm, the average equivalent circle diameter of the primary Si inside the powder particles is not greater than 30 μm, the average aspect ratio is not greater than 1.8, and the average roundness is not less than 0.60.